Pengaruh Model Pembelajaran VCT Berbantuan Media Canva Terhadap Hasil Belajar PPKn Siswa Kelas V - Tuken, Ritha; Israwaty, Ila; Ulfah, Rahmiana (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research aims to find out if there is no influence of VCT learning model supported by canva media on the learning outcomes of Polewali Mandar district Pekkabata State SD Class V students. The approach used in this research is a quantitative approach with the research design of Quasi Experiment in the form of Nonequivalent Control Group Design. The population in this study is the entire student SD State 066 Pekkabata, while the sample is the class V Sandeq as an experimental class and class V Andi depu as a control class with a simple number of 52 students. The results of the research were obtained after the pre-test and post-test. The results are obtained from the learning hassil of PPKn students. The result of inferential analytics with the Independent Sample T-test shows Sig (2 - tailed) = 0,000 < 0.05, so H0 is rejected and H1 is accepted. Thus, the conclusion of this study is that the VCT learning model supported by media canva has an influence on the improvement of learning outcomes of V Class Students of SD State 066 Pekkabata district of Polewali Mandar.